1986
DOI: 10.1137/0215023
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Point Location in a Monotone Subdivision

Abstract: Point location, often known in graphics as "hit detection," is one of the fundamental problems of computational geometry. In a point location query we want to identify which of a given collection of geometric objects contains a particular point. Let denote a subdivision of the Euclidean plane into monotone regions by a straight-line graph of m edges. In this paper we exhibit a substantial refinement of the technique of Lee and Preparata [SIAM J. Comput., 6 (1977), pp. 594-606] for locating a point in 5e based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
250
0
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 435 publications
(256 citation statements)
references
References 14 publications
1
250
0
2
Order By: Relevance
“…As an arrangement of m lines in the plane results in O(m 2 ) edges, the number of half-edges in DCEL(S) also is O(m 2 ). We can, in time O(m 2 ), preprocess U (S) into a structure that allows point location in O(log m) time [33]. Therefor, testing for each of the O(m 2 ) centers of mass whether they are part of the input takes O(m 2 log m).…”
Section: Property 2 (Quadratic Output Complexity)mentioning
confidence: 99%
See 2 more Smart Citations
“…As an arrangement of m lines in the plane results in O(m 2 ) edges, the number of half-edges in DCEL(S) also is O(m 2 ). We can, in time O(m 2 ), preprocess U (S) into a structure that allows point location in O(log m) time [33]. Therefor, testing for each of the O(m 2 ) centers of mass whether they are part of the input takes O(m 2 log m).…”
Section: Property 2 (Quadratic Output Complexity)mentioning
confidence: 99%
“…The time needed for checking whether an atomic object exists at some time moment and computing the snapshot (a triangle) is z(d, ). Because of the preprocessing on the snapshot at time moment J 1 , testing the barycenter of the triangle against that snapshot can be done in O(log n K ) time [33]. In case the snapshots are the same, adjusting the time domains of all atomic objects takes time O( n K ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At node ν, we store a point-location data structure [12] Proof To report all o * i intersecting s we walk down T , only visiting the nodes ν such that s intersects U(ν). This way we end up in the leaves corresponding to the o * i intersecting s. To decide if we have to visit a child ν of an already visited node, we do a point location with both endpoints of s in the trapezoidal map of U(ν).…”
Section: Objects With Small Union Complexity In Rmentioning
confidence: 99%
“…When the points are in convex position and given in clockwise order, Aggarwal et al [AGSS89] showed that either Voronoi diagram can be constructed in linear time. Answering point-location queries in either Voronoi diagram of points in convex position can be done in O(log n) time using O(n) preprocessing and space [EGS86].…”
Section: A Simple Data Structurementioning
confidence: 99%